Introduction to crystallography - Sands, Donald, 1929- (Dover, 1993)
Concise explanation of the logical development of basic crystallographic concepts. Extensive discussion of crystals and lattices, symmetry, crystal systems and geometry, x-ray diffraction, determination of atomic positions, and more. Well-chosen selection of problems, with answers. Ideal for crystallography course or as supplement to physical chemistry courses. 114 illustrations.
Originally published: Reading, Mass. : W.A. Benjamin, 1969 (corrected printing 1975) (Physical chemistry monograph series).
Keywords: Crystallography.; elektronické knihy; electronic books